Effect of Cd2+ on the Electrochemical Activity and Spectroscopic Property of Horseradish Peroxidase in the Simulated Physiological Solution - Guo, S.F.; Wang, Y.; Li, X.L.; Xie, B.D.; Yu, X.X. (Asian Journal of Chemistry, 2013)
The effect of Cd2+ on horseradish peroxidase (HRP) electrochemical activity and spectroscopic property in the simulated physiological solution was investigated by using the electrochemical techniques and spectroscopic methods. In this work, Cd2+ could interact with the amide groups of the peptide of the horseradish peroxidase molecules, leading to the change in the conformation of horseradish peroxidase. In which the interaction between Cd2+ and horseradish peroxidase molecules would lead to the decrease in the contents of a-helix and b-sheet and the increase in the content of the b-turn and random coil as well as the decrease in the content of hydrogen bonds inter- and intra-peptide chain in horseradish peroxidase molecules. This change would increase the planarity of porphyrin cycle in heme group and decrease the exposure extent of heme active center, Fe(III). The decrease in the exposure extent of heme active center would significantly decrease the catalytic and electrochemical activities of horseradish peroxidase.